Acknowledging Hybridity - Váró, Kata Anna (Hungarian Journal of English and American Studies, 2020)
Book review:Oliete-Aldea, Elena. Hybrid Heritage on Screen: The “Raj Revival” in the Thatcher Era. Houndmills, Basingstoke: Palgrave Macmillan, 2015. ix + 227 pages. ISBN 978-1-137-46396-8. $95.00.